Trends in the Brazil/Malvinas Confluence region. Issue 24 (18th December 2014) - Combes, Vincent; Matano, Ricardo P.
Abstract Observations show abrupt changes in the oceanic circulation of the southwestern Atlantic. These studies report a southward drift of the Brazil/Malvinas Confluence (BMC) and a change in the spectral characteristics of the Malvinas Current (MC) transport. We address the cause of these changes using the result of a high‐resolution numerical experiment. The experiment, which is consistent with observations, shows a southward BMC displacement at a rate of 0.62°/decade between 1993 and 2008, and a shift of the spectral characteristics of the MC transport after 1999. We find that these changes are driven by a weakening of the northern branch of the Antarctic Circumpolar Current, which translates to a weakening of the MC transport and a southward BMC drift. The drift changes the spectral characteristics of the MC transport, which becomes more influenced by annual and semiannual variations associated with the BMC.